Analisis Pengaruh Dana Transfer Daerah terhadap Ketimpangan Pendapatan melalui Pertumbuhan Ekonomi di Kabupaten Kutai Kartanegara - Achsani Taqwim Dwi Affan; Juliansyah Roy; Diana Lestari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of regional transfer funds on income inequality through economic growth as a mediating variable in Kutai Kartanegara Regency. Using a quantitative explanatory approach, the research employed time-series secondary data for the 2010–2024 period sourced from Statistics Indonesia (BPS) and the Ministry of Finance. The data were analyzed using path analysis with three regression models and the Sobel test to examine the mediation effect. The results show that regional transfer funds (Revenue Sharing Fund/DBH, General Allocation Fund/DAU, Special Allocation Fund/DAK, and Provincial Financial Assistance) do not simultaneously have a significant effect on economic growth, while economic growth itself has no significant effect on income inequality. In the direct-effect model, DAU significantly widens inequality, whereas DAK significantly reduces it. The Sobel test confirms that economic growth fails to mediate the effect of regional transfer funds on income inequality (all p-values > 0.05). These findings indicate that the relationship between transfer funds and inequality is predominantly direct rather than transmitted through macroeconomic growth, reflecting a structural bottleneck in a resource-dependent region. Inequality reduction must therefore rely on directly targeted, pro-equity fiscal spending rather than aggregate economic growth.